Cellular growth in different bioreactors to rabies virus production - Lantieri, V. S.; Medeiros, F. M.; Frazatti-Gallina, N. M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The scaling up of virus production process involves different challenges, mainly when is used an animal cells origin with a substrate. The growing of the animal cells in high densities depends on the beads and these cells present high susceptibility to the shear stress that occurs in the process realized in bioreactors. The objective of this study was to evaluate the growing of Vero cells in the scaling up process of rabies virus production in bioreactor. Two bioreactors were used in this study, one of 30 L (Bio Flow 4500, NBS) and other of 150 L (Bio Flo PRO Industrial, NBS). These bioreactors have different agitation systems: while the 30 L has a “Cell Lift Impeller”, the industrial, one STR, has pitched blade impellers. This difference was important to select the velocity of agitation necessary to maintain the beads in suspension and to minimize the shear stress and bead collisions. Vero cells added to solid microcarriers, Cytodex 1 (2g/L), infected with PV rabies virus (MOI 0,02) were cultivated in serum-free medium VP SFM AGT in the two bioreactors. Were realized seven cycles in each bioreactor type and the initial cellular concentration was 13-14 cell/microcarrier. Supernatants of these cultures were harvested on days 2 and 3 after start the cycle of production. Samples of these cultures were taken every day during the production cycle to determine the cellular concentration. It was studied too the cellular loss in the first day after the cell inoculation to analyze the cell difficulty for spread on the microcarriers. The averages of the values of cell specific grow rate found before the harvest beginning were 0.025 h-1 and 0.023 h-1 in the industrial and 30 L bioreactors respectively. The percentage averages of cellular loss in the first day after cell inoculation were 37% (± 16%) in the industrial bioreactor and 52% (± 21%) in the bioreactor of 30 L. The analyze of the data found to cell specific grow rate and cellular loss in the rabies virus production cycles showed that the spread and growth cellular were not affected by the blades of the impeller of industrial bioreactor. In conclusion, the expansion of Vero cell growth for rabies virus production in bioreactor of 150L was satisfactory because in this system the values of cellular loss and cell specific growth rate were similar or better than the values found in the 30 L bioreactor.